Apariția statului modern italian și problema „întârzierii istorice” (The establishing of the Italian Modern State and the problem of ”the historical delay”) - Ioana CRISTEA DRĂGULIN (Polis: Revista de Stiinte Politice, 2015)
The Italian State is an early creation. With a history of millennia, the people living in the Italian peninsula have managed to establish a modern state in mid-nineteenth century, compared with other European states (the French state, the English state etc.). This historical process have been known as „Risorgimento”. During this brief study I will present the problems which the state's founding fathers have experienced in the administrative centralization process in relation with the "ideal modern state pattern".